Análise da relação entre a taxa de câmbio e a arrecadação de ICMS para os Estados Nordestinos: uma abordagem em séries temporais para os anos de 2002 A 2011. - Barros, Ederian dos Santos (2014)
The aim of this work is analyzed the relationship between the ICMS revenue by Northeast Brazilian states and the exchange rate. The ICMS is a tax that is applied under imports and these are affect by exchange rate changes. If the Marshall-Lerner condition is accepted, a devaluation in the exchange rate reduces the imports. To investigate whether this channel is important to determine the ICMS revenue we used two methodologies: short run methodology based on impulse response function obtained from a VEC estimation; long run methodology based on Johansen’s cointegration tests. The results showed that the short run effect of exchange rate under the ICMS revenue was expected, at the period from 2002 to 2011. That is, a depreciation of the exchange rate reduces the ICMS imports. However, the long run effects could not be confirmed.